2017
DOI: 10.1177/1203475417745825
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Clustering of Cutaneous T-Cell Lymphoma (CTCL) Cases in Canada During 1992 to 2010

Abstract: Detailed analysis of CTCL incidence in Canada is critical to fully understand the burden of this disease in our country, to begin the search for a possible external trigger for this lymphoma, and to reform how health care resources are distributed throughout the country to better serve Canadian patients with CTCL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 29 publications
0
36
1
Order By: Relevance
“…In addition, in accordance with the institutional policy, this study received an exemption from the McGill University Research Ethics Board review. We examined the data on incidence and mortality of AML using 3 distinct population‐based cancer databases (Canadian Cancer Registry [CCR], Le Registre Québécois du Cancer [LRQC], and Canadian Vital Statistics [CVS]) for the period 1992‐2010 using International Classification of Diseases for Oncology ICD‐O‐3 codes for all subtypes of AML in a manner similar to that reported previously . Detailed methods are provided in Supporting Appendix 1.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, in accordance with the institutional policy, this study received an exemption from the McGill University Research Ethics Board review. We examined the data on incidence and mortality of AML using 3 distinct population‐based cancer databases (Canadian Cancer Registry [CCR], Le Registre Québécois du Cancer [LRQC], and Canadian Vital Statistics [CVS]) for the period 1992‐2010 using International Classification of Diseases for Oncology ICD‐O‐3 codes for all subtypes of AML in a manner similar to that reported previously . Detailed methods are provided in Supporting Appendix 1.…”
Section: Methodsmentioning
confidence: 99%
“…The epidemiology of AML in Canada is yet to be fully described and remains poorly understood. Several risk factors have been implicated in leukemogenesis, including occupational exposure to radiation, solvents, and chemicals such as benzene and formaldehyde; exposure to certain chemotherapy agents (eg, mechlorethamine, procarbazine, chlorambucil, melphalan, etoposide, teniposide and cyclophosphamide); and lifestyle factors such as obesity and smoking . Many of these risk factors have been identified through cluster analyses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clues pointing to attribution of environmental exposure include the concomitant rise in CTCL cases with industrial expansion, increased incidence in nonblood‐related relatives, and known associations of occupational chemicals with other hematologic malignancies . Clustering has been identified in several studies across the globe, including Sweden, Canada, Pittsburgh, Pennsylvania, and Texas . The analysis in Texas found 3 communities in metropolitan Houston with rates of CTCL that were between 5 and 20 times higher than the expected population rate .…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we extensively analyzed the epidemiology of PV patients in Canada and found a significant clustering of PV cases in specific Canadian communities. Such epidemiological analyses may shed light on potential risk factors as possible triggers/promoters of this malignancy …”
Section: Introductionmentioning
confidence: 99%